Systematic Literature Review: Pengaruh Psychological Capital terhadap Job Performance pada Karyawan Gen Milenial - Qonita Aristawidya Putri; Abdul Muhid (Jurnal Ilmu Manajemen, 2025)
The changing dynamics of the modern workplace demand that organizations manage human resources not only from a technical perspective but also from a psychological one. Psychological capital (PsyCap), which includes hope, self-efficacy, resilience, and optimism, has become an essential asset in supporting job performance, particularly among millennial employees who now dominate the workforce. This study aims to systematically examine the influence of PsyCap on the job performance of millennial employees using the Systematic Literature Review (SLR) method. Literature was collected from the Google Scholar and ScienceDirect databases, resulting in 14,619 articles that were filtered based on specific inclusion criteria, ultimately narrowing down to 5 primary articles. The findings indicate that PsyCap has a positive and significant impact on job performance. Several studies also identified mediating variables such as work engagement that strengthen the relationship between PsyCap and job performance. This study emphasizes that strengthening PsyCap through psychological interventions and supportive work environments can be an effective strategy for improving the job performance of millennial employees.